PELAKSANAAN KEBIJAKAN PERATURAN DAERAH KOTA SEMARANG NO. 11 TAHUN 2000 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KAWASAN JALAN PANDANARAN SEMARANG - Muhammad Fawwaz; Zainal Hidayat (Journal of Public Policy and Management Review, 2018)
The permissive policy of Semarang City stakeholders in the Pandanaran Road area is not accompanied by efforts to regulate and guide street vendors in accordance with the content of the policy, making the area less organized. The limitation of the relocation space for street vendors, to the problem of business place legality becomes a problem in efforts to achieve orderliness. This study aims to explain the implementation of Regional Regulation No. 11 of 2000 in the area of Jalan Pandanaran. In an effort to achieve orderliness, the provisions of the Mayor of Semarang number 511.3/1112/2016 did not designate the Jalan Pandanaran area for any business actor to trade. By using qualitative descriptive methods, participatory data collection techniques and in-depth interviews, data analysis and interpretation using taxonomic analysis, and data validation using trianggulation techniques, this study managed to draw the conclusion that irregularities in the Pandanaran Road area were caused by the of firm policy implementation carried out by policy implementers in the region. For this reason, it is necessary to use persuasive approaches, coordination between stakeholders, and consistency in the implementation of policies by the implementor.